DEVELOPMENT AND CHARACTERIZATION OF MUCOADHESIVE MICROSPHERE-LOADED INTRANASAL GEL OF VENLAFAXINE HYDROCHLORIDE - Kalita, Bhupen; Saikia, Kritika; Kalita, Banasmita (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The main objective of the present work is to develop and characterize a novel mucoadhesive intranasal microsphere gel formulation of drug venlafaxine to control the drug release through nasal mucosa and reach the target site with minimal side effect. The objectives of the study are (1) formulation of mucoadhesive microspheres, (2) evaluation of mucoadhesive microspheres, (3) formulation of mucoadhesive microsphereloaded nasal gel, (4) and evaluation of nasal gel. Methods: Preparation of chitosan microsphere: The chitosan microspheres were prepared by emulsion cross-linking method. Preparation of microsphere-loaded gel: The nasal gels with varying concentrations of Carbopol 934P were prepared by dispersing required quantity of Carbopol in required quantity of distilled water with continuous stirring and kept overnight for complete hydration. The gel was then modified by the addition of varying proportion of hydroxypropyl methylcellulose (HPMC) K4M. Results: The prepared microspheres were evaluated for size distribution, surface morphology by scanning electron microscopy, entrapment efficiency, compatibility by Fourier transform infrared spectroscopy, and differential scanning calorimetry. Entrapment efficiency of all formulations was found more than 70%. Microsphere formulation containing drug and polymer in the ratio of 1:2.5 was found to be optimized. Optimized microsphere formulation was then incorporated in gel prepared using Carbopol 934P and HPMC. Prepared gel formulations were studied for viscosity, spreadability, and in-vitro drug release in simulated nasal conditions. Viscosity of the optimized batch of gel was recorded at 1056 centipoise. Drug release was prolonged for the microsphere-in-gel formulations compared to the microspheres alone. For the optimized batch of gel, cumulative drug release of 85.67% was found after 8 hrs. Conclusion: The results suggest that venlafaxine hydrochloride mucoadhesive microsphere-loaded nasal gel would give sustained drug release and superior bioavailability in the brain sites. Keywords: Venlafaxine, Chitosan, Mucoadhesive, Microsphere, Nasal gel.